Forms of Presentation of the Sandur Manduro Mask Dance - Nur Aldilla; Handayaningrum, Warih (Solah, 2025)
The Bapang Sandur Manduro Mask Dance is a single dance that is part of the Sandur Manduro performance, which developed in the area of Kabuh District, Jombang Regency. The dance features firm and simple movements, reflecting the character of the local people who are known for being brave and a little haughty. This study aims to examine the form of presentation of the Bapang Sandur Manduro Mask Dance using the theoretical approach of the form of presentation. This study uses a qualitative method, with data collection techniques in the form of field observations, in-depth interviews, and documentation. The data analysis process is carried out through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that this form of dance presentation has its own uniqueness, which comes from the local culture of the Manduro people and the personal style of the dancers. Elements of local culture are reflected through various elements such as stage arrangements, costumes, use of masks, musical composition, and movement patterns. In addition, the dance style is also influenced by the dancer's body expression, which emphasizes strong and distinctive movements, with individual characteristics such as body rotation and movements that tend to be limited.